LA UNIDAD DE LA CIENCIA Y LA RELEVANCIA DE LA INVESTIGACIÓN - Jensen Pennington, Henning (2001)
The author discusses different aspects of scientific organization in developing countries, making special reference to Costa Rica, and argues in favor of the cooperation between disciplines in order to cope with social problems of particular significance. It follows a brief critical discussion of the idea of unity of scientific knowledge, as well as of the concept of relevance of scientific theories. Referring explicitly to discourse ethics, the author concludes with some thoughts on the articulation between research and citizen ethics.